(untitled) (Journal of actual problems of jurisprudence, 2016)
Transition to environmentally sound and sustainable development is now becoming one of the priorities of Kazakhstan’s development strategy. Environmental Policy of the Republic of Kazakhstan is developing in these areas and set a goal of protecting the environment and managing natural resources ispolzvanie. These objectives are set out in specific regulations. This article discusses the problem of the formation and development of the legal foundations of the environmental policy of the Republic of Kazakhstan.